Islet coordinately regulates motor axon guidance and dendrite targeting through the Frazzled/DCC receptor - Santiago, Celine (Cell Rep, 2017)
Motor neuron axon targeting in the periphery is correlated with the positions of motor neuron inputs in the CNS, but how these processes are coordinated to form a myotopic map remains poorly understood. We show that the LIM homeodomain factor Islet (Isl) controls targeting of both axons and dendrites in Drosophila motor neurons through regulation of the Frazzled (Fra)/DCC receptor. Isl is required for fra expression in ventrally-projecting motor neurons, and isl and fra mutants have similar axon guidance defects. Single-cell labeling indicates that isl and fra are also required for dendrite targeting in a subset-specific way. Finally, over-expression of Fra rescues axon and dendrite targeting defects in isl mutants. These results indicate that Fra acts downstream of Islet in both the periphery and the CNS, demonstrating how a single regulatory relationship is used in multiple cellular compartments to coordinate neural circuit wiring.